Report from the Eighth Agent-Oriented Software Engineering Workshop, AAMAS 2007. (14th December 2007) - Luck, Michael; Padgham, Lin
This paper provides a brief report on the Eighth International Workshop on Agent Oriented Software Engineering, held in Honolulu, Hawaii, at the AAMAS conference, in May 2007. A post-proceedings will be published by Springer-Verlag in the LNCS series, with extended papers which take into account discussion and interaction at the workshop. This report provides a brief summary of the presentations and discussion at the workshop, with particular emphasis on trying to capture some of the interactive discussion which took place.